Superhydrophobic surfaces - Crawford, Russell J.; Ivanova, Elena P. (Amsterdam, Netherlands : Elsevier, 2015)
Superhydrophobic Surfaces analyzes the fundamental concepts of superhydrophobicity and gives insight into the design of superhydrophobic surfaces. The book serves as a reference for the manufacturing of materials with superior water-repellency, self-cleaning, anti-icing and corrosion resistance. It thoroughly discusses many types of hydrophobic surfaces such as natural superhydrophobic surfaces, superhydrophobic polymers, metallic superhydrophobic surfaces, biological interfaces, and advanced/hybrid superhydrophobic surfaces. Provides an adequate blend of complex engineering concepts with in.
Bacterial interactions with superhydrophobic surfaceseukaryotic cell-tissue interactions with superhydrophobic surfaces; summary; references; index
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Hydrophobic surfaces; Surface chemistry; Wetting; SCIENCE / Chemistry / Physical & Theoretical; Hydrophobic surfaces; Surface chemistry; Wetting; Hydrophobe Wechselwirkung; Oberflhe; Electronic books; Electronic books